Effectiveness of photodynamic therapy associated with irrigants over two biofilm models - Rosa, Ricardo Abreu da; Santini, Manuela Favarin; Poli de Figueiredo, Jose Antonio; Visioli, Fernando.; Pereira, Jefferson Ricardo; Vivan, Rodrigo Ricci [UNESP]; Montagner, Francisco; Reis So, Marcus Vinicius (Elsevier B.V., 2017)
Background: This study aimed to evaluate the antibacterial effect and the biofilm disruption promoted by antimicrobial photodynamic therapy (aPDT) associated with sodium hypochlorite (NaOCl) and chiorexidine (CHX) over monospecies and multispecies biofilms. Methods: In monospecies model, forty-six premolars were inoculated with Enterococcus faecalis for 21 days and divided into three groups: saline, CHX and NaOCl. After irrigation, aPDT was performed. Samples were collected at baseline (S1) and after irrigation (S2) and aPDT (S3). Colony-forming unit (CFU) counts were performed. In multispecies model, sixty bovine dentin blocks were infected intraorally for 72 h and divided into six groups: saline, saline/aPDT, CHX, CHX/aPDT, NaOCl and NaOCl/aPDT. The percentage and the biovolume of live cells and the total biovolume were assessed using confocal laser scanning microscopy. Results: CHX and NaOCl showed the lowest CFU counts (P < 0.05). aPDT reduced the bacterial counts in saline (S2-S3; P < 0.05). The lowest amount of live cells was observed in CHX, CHX/aPDT, NaOCl and NaOCl/aPDT. aPDT did not reduce the total biovolume (P > 0.05). Conclusion: aPDT associated with saline reduced the bacterial load in root canals infected with E. faecalis. aPDT did not reduce the total biovolume in situ; however, the irrigant was decisive to disrupt multispecies biofilms.
Keywords: Photodynamic therapy; Enterococcus faecalis; Root canal irrigants; Biofilm; Confocal laser scanning microscopy